Papillary Fibroelastoma Found With Transesophageal Echocardiography After a Normal Transthoracic Echocardiography. (September 2017) - Cook, Andrew G.; Viswanath, Omar; D'Mello, Jayanand
We present the case of a patient with transient ischemic attacks who was being investigated for multiple embolic strokes. Initial workup, including brain computed tomography, computed tomography angiography, and transthoracic echocardiography (TTE) were negative for a source until transesophageal echocardiography (TEE) found a mass in the left atrium. The TEE differentiated the mass as a rare cardiac papillary fibroelastoma on the left atrial free wall confirmed by postsurgical pathology. This case highlights the importance of TEE as a diagnostic tool for its ability to more accurately differentiate and characterize the tumor compared with TTE. This case underscores that a negative TTE does not equate to zero risk of the presence of a cardiac tumor. It is prudent for the clinician to be cognizant that it may be beneficial to perform a TEE even with a negative TTE workup.